Dosage Sensitivity of RPL9 and Concerted Evolution of Ribosomal Protein Genes in Plants - Devis, Deborah; Firth, Sue M.; Liang, Zhe; Byrne, Mary E. (Frontiers in Plant Science, 2015)
The ribosome in higher eukaryotes is a large macromolecular complex composed of four rRNAs and eighty different ribosomal proteins. In plants, each ribosomal protein is encoded by multiple genes. Duplicate genes within a family are often necessary to provide a threshold dose of a ribosomal protein but in some instances appear to have non-redundant functions. Here, we addressed whether divergent members of the RPL9 gene family are dosage sensitive or whether these genes have non-overlapping functions. The RPL9 family in A. thaliana comprises two nearly identical members, RPL9B and RPL9C, and a more divergent member, RPL9D. Mutations in RPL9C and RPL9D genes leads to delayed growth early in development, and loss of both genes is embryo lethal, indicating that these are dosage-sensitive and redundant genes. Phylogenetic analysis of RPL9 as well as RPL4, RPL5, RPL27a, RPL36a and RPS6 family genes in the Brassicaceae indicated that multicopy ribosomal protein genes have been largely retained following whole genome duplication. However, these gene families also show instances of tandem duplication, small scale deletion and evidence of gene conversion. Furthermore, phylogenetic analysis of RPL9 genes in angiosperm species showed that genes within a species are more closely related to each other than to RPL9 genes in other species, suggesting ribosomal protein genes undergo convergent evolution. Our analysis indicates that ribosomal protein gene retention following whole genome duplication contributes to the number of genes in a family. However, small scale rearrangements influence copy number and likely drive concerted evolution of these dosage-sensitive genes.